Jamaica’s Climate Change Research Agenda - Lanza Castillo, Gracia María (2022)
With the support of the Climate Technology Centre and Network (CTCN), the first phase of defining a road map for targeted research in Jamaica began in September 2020. During the development process, an effort was made to identify and analyse existing capacities in universities, research centres, and the private sector, whose lines of work support climate change priorities and the development of technological capacities in productive activities. This document presents an agenda for research and technology development (RT&D), the result of a co-creation process with academia, R&TD centres, and the private sector, to support climate change targets in the key sectors identified for the first phase: agriculture and fisheries, water, human settlement and infrastructure, waste, and energy. The sectors were prioritised using a multicriteria analysis that took account of the need for new knowledge to address climate change impact-related issues, as well as the importance of each sector in terms of economic impact, climate, environmental, and social impact.